A novel synthesis of CZTS quantum dots using pulsed laser irradiation. (September 2017) - Najafi, Vahid; Aghelifar, Mehrnoush; Kimiagar, Salimeh
Abstract: In present study, a non-colloidal method proposed to produce CZTS quantum dot (QDs) by using pulsed laser irradiations. In this method the QDs size were accurately controlled by selecting the appropriate laser energy. Results showed that the optimum size of CZTS QDs was achieved at 80 mJ energy for 15 min laser irradiations. Uniform size distribution, increasing of speed and amount of CZTS QDs production were considered as advantages of this method. These CZTS QDs were applied in three different quantum dot-sensitized solar cells. The best efficiency obtained for FTO/TiO2+ZrO2+GO/CZTS QDs/Polysulfide/CuS/FTO cell structure about 1.438%. Abstract : CZTS quantum dot (QDs) was produced using pulsed laser irradiations. The size was accurately controlled by laser energy. Results showed that the optimum size of CZTS QDs was achieved at 80 mJ energy for 15 min laser irradiations. The best efficiency obtained for FTO/TiO2+ZrO2+GO/CZTS QDs/Polysulfide/CuS/FTO solar cell structure about 1.438%.